Perancangan Sistem Informasi Manajemen Wisuda Terintegrasi Politeknik Negeri Subang Berbasis Website - Mubarak, Fadlla; Khoirunnisa, Nurfitria; Azhariyah, Sari (Jurusan Teknik Komputer, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
Abstract: This study aims to design Sistem Manajemen Wisuda Terintegrasi (SIMUDA POLSUB) at Politeknik Negeri Subang. The primary objective of this system is to address common issues in the data management of graduates, the submission of SKBA, and the online management of invitations, which ultimately can reduce queues accelerate the process during graduation ceremonies. With the implementation of this system, the entire graduation administration process is expected to become more organized. In this research, the methodology used is the Waterfall model, with primary focus on the analysis and design stages. The research conducted at State Polytechnic of Subang with participants including academic administrators, graduates, department heads, treasurers, librarians, departmental admin, and graduation committees. Data collection performed through various techniques including observation, in-depth interviews, and literature studies to identify in detail the user needs and technical requirements of system. The data collected translated into system design that includes Usecase Diagrams, Activity Diagrams, and Sequence Diagrams. Data analysis was systematically performed to ensure the resulting design could meet all identified needs. The results of study show that the design of SIMUDA POLSUB successfully automated the data management processes graduates, submission of SKBA, and management invitations. The comprehensive integration graduation administration processes into single web application, customized specifically for the needs of State Polytechnic of Subang, demonstrates an innovation in higher education management. Based on these results, it is recommended that system be adopted and implemented more widely in educational institutions to improve the graduation administration process.Abstrak: Penelitian ini bertujuan untuk merancang Sistem Manajemen Wisuda Terintegrasi (SIMUDA POLSUB) di Politeknik Negeri Subang. Tujuan utama dari sistem ini adalah untuk mengatasi permasalahan yang sering terjadi dalam pendataan wisudawan, pengajuan Surat Keterangan Bebas Akademik (SKBA), dan pengelolaan undangan secara online, yang pada akhirnya dapat mengurangi antrian dan mempercepat proses saat acara wisuda. Dengan perancangan sistem ini, diharapkan dapat menggambarkan seluruh proses administrasi wisuda menjadi lebih terorganisir. Pengumpulan data dilakukan melalui beberapa teknik yang meliputi observasi, wawancara mendalam, dan studi literatur untuk mengidentifikasi secara detail kebutuhan di politeknik negeri subang. Hasil dari pengumpulan data ini kemudian diterjemahkan ke dalam desain sistem yang meliputi Use Case Diagram, Activity Diagram, dan Sequence Diagram. Analisis data dilakukan secara sistematis untuk memastikan bahwa desain yang dihasilkan dapat memenuhi semua kebutuhan yang telah teridentifikasi. Hasil penelitian ini menunjukkan bahwa perancangan SIMUDA POLSUB berhasil menggambarkan proses sinkronisasi pendataan wisudawan, pengajuan SKBA, dan pengelolaan undangan. Integrasi yang terhubung dengan SIAKAD POLSUB untuk pengolahan pendataan wisudawan Politeknik Negeri Subang menunjukkan sebuah inovasi dalam manajemen pendidikan tinggi. Berdasarkan hasil tersebut, disarankan agar sistem ini diadopsi dan di implementasi secara lebih luas di institusi pendidikan untuk memperbaiki proses administrasi wisuda.